Phytochemical Analysis and Antibacterial Activity of Clitoria ternatea against Escherichia coli - Tai Qian Yun,; Pa'ee, Furzani (Journal of Sustainable Natural Resources, 2022)
Medicinal plants had long been utilized by humans to treat various ailments, including bacterial-caused diarrhea. Nowadays, issues related to the use of antibiotic including emergence of resistant bacteria and side-effects associated with synthetic antibiotic urge the finding of novel antibacterial substances from natural sources that are deemed more effective and safer. Clitoria ternatea is traditionally used as medicine in Ayurveda and had been found to exhibit antibacterial activities due to its rich phytochemical contents. In this study, the methanolic C. ternatea leaves extracts were investigated for phytochemical content and antibacterial activity. Phytochemical content was investigated quantitatively focusing on total phenolic content (TPC) and total flavonoid content (TFC). The TPC was determined by Folin-Ciocalteau method, and the TFC was determined by Aluminum-chloride method. Disk-diffusion method was used to analyze the antibacterial potential of the plant extract in four different concentrations (12.5, 25, 50, 100 mg/mL), ampicillin was used as positive control and methanol as negative control. The extraction yield of methanolic C. ternatea leaves extracts obtained by maceration method is 8.16%. The TPC and TFC of C. ternatea leaves extract are 0.66116 Â± 0.43455 GAE mg/g and 0.31333 Â± 0.057735 QE mg/g respectively. The disk-diffusion antibacterial assay showed no inhibitory activity of C. ternatea extracts against Escherichia coli. This might be attributed to the lack of potency of C. ternatea extracts at their current concentration, due to the low content of TPC and TFC in the extracts. This had partially proved that concentration of the extracts used is crucial in antibacterial activities. Review on precedent studies revealed that different methodologies caused discrepancy of antibacterial results in C. ternatea extract. In conclusion, C. ternatea has been seen as a high potential plant in terms of antibacterial activity, but conditions during experiment poses high impact on the result of antibacterial assay. The findings from this study had provided valuable information to the related fields.